The Mediating Role of Work Motivation in the Impact of Training on Teachers’ Digital Literacy - Butar Butar, Senita; Mulyadi, Hari; Ramdhany, Muhamad Arief (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
It is importance of improving the digital literacy of teachers is crucial with the rapid integration of technology in education, effective training programs are critical. However, their success largely depends on the motivation of the participants. The purpose of this study is to determine the mediating role of the work motivation variable on the effect of the training variable on the digital literacy variable so that there are two independent variables and one dependent variable. The number of samples used was 73 teachers in Palembang. To collect data, a questionnaire technique was used. Using the Smart PLS 3.0 structural equation modeling technique, the hypothesized relationships in this study were tested. This study found that: 1) training had a positive and significant effect on teacher motivation; 2) work motivation had a positive and significant effect on teacher digital literacy; 3) training had a positive and significant effect on teacher digital literacy; and 4) work motivation had a mediating effect on the relationship between training and teacher digital literacy. These results highlight the importance of fostering a motivational climate to maximize the benefits of training programs. Implications for educational policy and practice are discussed, emphasizing the need for strategies that not only provide training but also actively engage and motivate teachers to enhance their digital competencies.